Enhancing social communication behaviors in children with autism: the impact of dog training intervention on verbal and non-verbal behaviors - Polak-Passy, Yaara; Ben-Itzchak, Esther; Zachor, Ditza A. (Frontiers in Psychology, 2024)
IntroductionThis study investigated the impact of dog training intervention (DTI) on verbal, non-verbal, and maladaptive behaviors in autistic preschoolers. Previous research has demonstrated the benefits of animal-assisted interventions, but this study specifically focused on changes during the DTI.MethodsWe analyzed video recordings of 37 autistic children (mean age 4:7 years, SD = 1:1) from special education preschools, comparing their behaviors during the initial and final intervention sessions. The intervention, consisting of 17 structured stages, progressively introduced the children to dog interactions, ultimately allowing them to act as dog trainers. Behavioral analysis was divided into two main areas: responses to the therapist’s instructions and self-initiated behaviors observed in interactions with the therapist and the dog.ResultsPost-intervention results indicated a notable increase in non-verbal communication, with more sustained self-initiated eye contact, gestures, and facial expressions and increased verbal commands directed toward the dog. Improvements were also seen in therapist-prompted gestures and joint attention, and question-answer interactions with the therapist. However, a decrease was observed in self-initiated eye contact, duration of eye contact, and verbal sharing with the therapist. Maladaptive behaviors, such as inappropriate physical contact and repetitive movements, decreased. The study found a moderate negative correlation between autism severity and responsiveness to therapist instructions and a moderate positive correlation between IQ and improvements in therapist responsiveness.DiscussionThese findings support the growing evidence for the efficacy of dog-assisted interventions and emphasize the importance of tailoring interventions to individual child characteristics.